Sensor array based determination of Edman degradated amino acids using poly(p-phenyleneethynylene)s - Zhang, Hao; Wang, Benhua; Seehafer, Kai; Bunz, Uwe H. F. (Chemistry - a European journal, 2020)
A cross-reactive optical sensor array based on poly(p-phenyleneethynylene)s (PPEs) determines Edman degraded amino acids. We report a sensor array composed of three anionic PPEs P1-P3, and their electrostatic complexes with metal ions (Fe2+, Cu2+, Co2+). We recorded distinct fluorescence intensity response patterns as “fingerprints” of this chemical tongue toward standard phenylthiohydantoin (PTH) amino acids—degradation products of the Edman process. These “fingerprints” were converted into canonical scores by linear discrimination analysis (LDA), which differentiates all of the PTH-amino acids. This array discriminates PTH-amino acid residues degraded from an oligopeptide through Edman sequencing. This approach is complementary to chromatography approaches which rely on mass spectrometry; our array offers the advantage of simplicity.